A Socio-Economic Perspective of B40 Household Budgets in Malaysia - HAMID, NADIAH ABD; YAACOB, ZAILAWATI; IBRAHIM, ZURAEDA; AZIZAN, SARINI; RASHID, NORFADZILAH (The journal of contemporary issues in business and government, 2021)
This paper explores the main determinants of the socio-economic characteristics in Malaysian households in terms of budget and income. Generally, the amount of expenditures depends on the changes in household budgets; thus, income and wealth are the primary determinants of household budgets and consequently consumption patterns. In the wake of Covid-19, Malaysia’s economy has been highly impacted and people were unable to run businesses or any economic activities except for those classified as essential services such as hospitality, medical, foods and beverages, and retailing. As such, these have impacted the people with lower income earnings, especially the Bottom 40, which is classified as those with household income median of RM3,000. The B40s spend their income mainly on life necessities whereby a higher saving rate would be an assurance for higher future consumption. In view of this, the government must play its role in helping the B40s fulfill their necessities through significant policies such as increasing the amount of Bantuan Sara Hidup (BSH), providing an old-age pension, and addressing poverty problems among B40s as well as drafting a long-term plan to mitigate these problems.